Analisis sistem dan prosedur pemungutan pajak parkir di Kota Manado - Tumbel, Glorya; Runtu, Treesje; Mintalangi, Syermi S. E. (Riset Akuntansi dan Portofolio Investasi, 2024)
Manado City is the capital of North Sulawesi Province and has enormous potential. One area that has not been explored is the potential for parking tax. This research was conducted at the Manado City Regional Revenue Agency with the clear objective of understanding the parking tax collection system and procedures in Manado City. This research employs a qualitative descriptive method. This research employs both qualitative and quantitative data. This research employs two data collection methods: interviews and documentation. This research has revealed that the parking tax collection system used is the self-assessment system. The parking tax collection procedure is carried out in accordance with Manado City Regional Regulation Number 2 of 2011 concerning Regional Taxes and Manado Mayor Regulation Number 57 of 2013 concerning Procedures for Collecting Regional Taxes. The new application from Bapenda must be adjusted to suit taxpayers and Bapenda employees. Secondly, there are still taxpayers who do not deposit their taxes according to the turnover they receive.